Otonomi Desa Dalam Pengelola Keuangan Berdasarkan Undang-Undang No 6 Tahun 2014 - I Wayan Wisadnya (Universitas Mahendradatta, 2019)
Village is as the lowest form of autonomous government, so that it can implement autonomyproperly, then the administration of its government must have the main factor that is said to beautonomous is the Human Resources factor as the executor, Financial factor, Supporting Infrastructureand Institutional Factors and Institution. Village Government whose existence is directly related to thecommunity and as the spearhead of development, the village government is increasingly required to beprepared both in terms of formulating village policies (in the form of village regulations), planningvillage development that is adapted to the situation conditions and in providing routine services to thecommunity. autonomous people must have the authority and ability to explore financial or revenuesources, manage and use their own finances, in other words there is independence or village autonomyin managing village budget and expenditure expenditure. which is the village's wealth, the compilationof the village's income and expenditure budget, the administration or administration of financial affairsand financial accountability. The problem in this research is whether the Village Law has givenautonomy to village finances, as well as the exercise of authority of the village government in realizingvillage autonomy. This research is a study using Normative Juridical research methods, using legalmaterials, namely the legislative approach and conceptual approach, is a normative analysis showingthat the authority of the village government is based on the principles and legal norms that apply, whilethe conceptual village financial management autonomy.